Phytochemical Investigations on Elaeagnus umbellata (Global Journal of Science Frontier Research, 2012)
- In the course of phytochemical investigations on methanol extract of Elaeagnus umbellata lead to the isolation of new isoflavone and phenol compound as a source from this plant. The isolation of plant also gave the terpenoid compound. The name of isolated compounds are; 3-(hydroxymethyl)-4-methoxyphenol (1) and 5, 7-dihydroxy-3(2-hydroxyphenyl-4H-chromen-4-one (1) and Stigmasterol (3). This is the first report of the isolation of compounds (1) and (2). The Characterization of the compounds was made on the basis of spectral studies.
Keywords: phytochemical; isoflavone; phenol and spectral studies